The contaminant legacy from historic coastal landfills and their potential as sources of diffuse pollution. (March 2018) - O'Shea, Francis T.; Cundy, Andrew B.; Spencer, Kate L.
Abstract: Prior to modern environmental regulation landfills in low-lying coastal environments were frequently constructed without leachate control, relying on natural attenuation within inter-tidal sediments to dilute and disperse contaminants reducing environmental impact. With sea level rise and coastal erosion these sites may now pose a pollution risk, yet have received little investigation. This work examines the extent of metal contamination in saltmarsh sediments surrounding a historic landfill in the UK. Patterns of sediment metal data suggest typical anthropogenic pollution chronologies for saltmarsh sediments in industrialised nations. However, many metals were also enriched at depth in close proximity to the landfill boundary and are indicative of a historical leachate plume. Though this total metal load is low, e.g., c. 1200 and 1650 kg Pb and Zn respectively, with > 1000 historic landfills on flood risk or eroding coastlines in the UK this could represent a significant, yet under-investigated, source of diffuse pollution. Highlights: Historic landfills were constructed prior to modern environmental regulation. Historic metal-rich leachate plumes have contaminated adjacent fine-grained marine sediments. This represents a small, but significant source of diffuse pollution in the coastal zone.